2019
DOI: 10.5430/wje.v9n3p30
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Teacher Feedback on the Simple Past Tense Acquisition in Senior High School Students' English Writing

Abstract: Teacher feedback is an essential part which can not be overlooked in English writing teaching. Whether teacher feedback is effective and which type of feedback is more effective in improving learners' writing proficiency have attracted more and more researchers' attention. Direct feedback is the feedback that teachers correct students' errors directly under the form or the right using habit of target language. Indirect feedback is the feedback that teachers only mark out or point out students' errors but not c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…In another study, students emphasized that they find teacher feedback more useful (Karlsen 2017). Both direct and indirect feedback from teachers was found to improve students' learning outcomes (Zhong et al 2019). Al-Hattami (2019) who conducted research on students in Bahrain Teachers College (BTC) identified the lack of constructive feedback as one of the reasons why the academic achievement of students are dwindling.…”
Section: Teachers' Assessment Feedbackmentioning
confidence: 99%
“…In another study, students emphasized that they find teacher feedback more useful (Karlsen 2017). Both direct and indirect feedback from teachers was found to improve students' learning outcomes (Zhong et al 2019). Al-Hattami (2019) who conducted research on students in Bahrain Teachers College (BTC) identified the lack of constructive feedback as one of the reasons why the academic achievement of students are dwindling.…”
Section: Teachers' Assessment Feedbackmentioning
confidence: 99%
“…More and more attention has been paid to English learning in recent years. However, compared to previous years, more errors have been found in ESL learners' writing assessment [2]. One of the most important reasons is the change in the English writing teaching approach.…”
Section: Introductionmentioning
confidence: 96%
“…One of the most important reasons is the change in the English writing teaching approach. The emphasis on the teaching of writing has shifted from grammar and words to content and logic [2]. According to them, this studentcentered approach can inspire learners' interests and motivation, but increase chances to make mistakes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A search into the literature indicates no agreement among the researchers and scholars as to what type, amount, and way of providing feedback to students shall be followed (Benson & DeKeyser, 2019). To date, several studies have been conducted to investigate these issues (e.g., (Bijami, Pandian, & Singh, 2016;Djumingin & Weda, 2019;Eva, McMorrow, Molloy, & Wilson, 2018;Lee, 2017;Mikulski, Elola, Padial, & Berry, 2019;Mishchenko, 2019;Yang, 2019;Zhong, Yan, & Zou, 2019)).…”
Section: Introductionmentioning
confidence: 99%